A positive electrode material, a positive electrode sheet, and a secondary battery
Patent Information
- Application Number
- CN202510536051.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-25
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]本发明的主要目的在于提供一种正极材料、正极片及二次电池,以解决现有技术中正极材料结构不稳定而导致容量下降和循环稳定性差的问题
[0019]应用本发明的技术方案,通过控制刻蚀时间为160秒、320秒、480秒中任意两个刻蚀时间处的晶格氧特征峰的峰位差值的绝对值≤0.1eV,说明正极材料在刻蚀时间为160秒、320秒和480秒处的晶格氧的电子结合能保持高度的一致性,晶格氧的稳定性高,保证了正极材料表层区域的均匀性和结构稳定性,确保正极材料在充放电过程中的稳定性和锂离子的脱嵌能力,在充放电过程中,该正极材料能够保持良好的电化学性能,避免了因结构不稳定而导致的容量衰减和循环稳定性下降的问题。
Smart Images

Figure CN122992052A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of secondary battery technology, and more specifically, to a positive electrode material, a positive electrode sheet, and a secondary battery. Background Technology
[0002] Lithium-ion batteries are widely used in 3C products, power devices, and energy storage equipment due to their advantages such as low self-discharge rate, high charge-discharge efficiency, no memory effect, and long cycle life. The cathode material is a crucial component of lithium-ion batteries, and its performance directly affects the electrochemical performance of the battery. With the widespread application of lithium-ion batteries, there is a need for cathode materials with high specific capacity, high safety, and low cost. Increasing the nickel content in the cathode material is a key strategy for achieving high energy density. However, with the increase of Ni content, the cathode material becomes sensitive to the environment during storage and easily accumulates residual alkaline compounds (such as LiOH and Li₂CO₃) on its surface. This not only leads to the loss of active lithium but may also trigger gelation during cathode slurry preparation, increasing manufacturing costs. Currently, most methods use water washing to reduce the residual alkaline content on the cathode material surface. However, during water washing, the surface reactivity of the cathode material increases, leading to the dissolution of a large amount of lattice lithium, which destroys the layered structure of the material. This not only reduces the battery capacity but also increases side reactions between the cathode material and the electrolyte, resulting in decreased cycle stability. Summary of the Invention
[0003] The main objective of this invention is to provide a positive electrode material, a positive electrode sheet, and a secondary battery to solve the problems of capacity reduction and poor cycle stability caused by the unstable structure of the positive electrode material in the prior art.
[0004] To achieve the above objectives, according to one aspect of the present invention, a cathode material is provided. The cathode material is etched by argon ions at an etching rate of 0.25 nm / s. X-ray photoelectron spectroscopy is used to characterize the etched cathode material. The cathode material exhibits lattice oxygen characteristic peaks at etching times of 160 seconds, 320 seconds, and 480 seconds. The absolute value of the peak position difference between any two lattice oxygen characteristic peaks at any two etching time points is ΔE. a And ΔE a ≤0.1eV.
[0005] Furthermore, the cathode material also exhibits characteristic peaks of active oxygen at etching times of 160 seconds, 320 seconds, and 480 seconds; among them,
[0006] At the same etching time, the peak intensity ratio of the active oxygen characteristic peak to the lattice oxygen characteristic peak is Z. i , where i is a natural integer; and, Z at any two etching time points i The absolute value of the difference is ΔZ, which satisfies ΔZ≤0.2.
[0007] Furthermore, at the same etching time point, the absolute value of the peak position difference between the lattice oxygen characteristic peak and the active oxygen characteristic peak of the cathode material is ΔE, which satisfies: ΔE≥1.8eV.
[0008] Furthermore, the impedance value of the positive electrode material is R, which satisfies R < 25Ω.
[0009] Furthermore, the mass content of free lithium in the cathode material is F, which satisfies F > 0.1%.
[0010] Furthermore, the peak positions of the lattice oxygen characteristic peak are 531–533 eV, and the peak positions of the active oxygen characteristic peak are 528–530 eV.
[0011] Furthermore, the chemical formulas of the cathode materials each independently include LiNi 1-x-y-z Co x Mn y M z O2, M includes at least one of Zr, Al, W, B, Sr, Y, Ti, S, P, 0≤x≤0.2, 0≤y≤0.5, 0≤z≤0.1.
[0012] Furthermore, the cathode material satisfies at least one of the following characteristics:
[0013] (1) The median particle size D50 of the volume distribution of the cathode material is 5-7 μm;
[0014] (2) The tap density of the positive electrode material is 2-3 g / cm³. 3 ;
[0015] (3) The compaction density of the positive electrode material is 3-4 g / cm³. 3 ;
[0016] (4) The specific surface area of the positive electrode material is 0.5–0.8 m². 2 / g.
[0017] A second aspect of the present invention provides a positive electrode sheet comprising the positive electrode material provided in the first aspect.
[0018] A third aspect of the present invention provides a secondary battery comprising the positive electrode provided in the second aspect.
[0019] By applying the technical solution of this invention, and controlling the absolute value of the peak position difference of the lattice oxygen characteristic peak at any two etching times of 160 seconds, 320 seconds, and 480 seconds to be ≤0.1 eV, it is shown that the electron binding energy of the lattice oxygen in the cathode material at etching times of 160 seconds, 320 seconds, and 480 seconds remains highly consistent, and the lattice oxygen has high stability. This ensures the uniformity and structural stability of the surface region of the cathode material, and ensures the stability of the cathode material and the lithium ion insertion / extraction capability during the charging and discharging process. During the charging and discharging process, the cathode material can maintain good electrochemical performance and avoid the problems of capacity decay and decreased cycle stability caused by structural instability. Attached Figure Description
[0020] Figure 1 This is a schematic diagram of the structure of a secondary battery during charging according to an embodiment of the present invention;
[0021] Figure 2 This is a schematic diagram of the structure of a secondary battery during discharge according to an embodiment of the present invention;
[0022] Figure 3 X-ray photoelectron spectroscopy of the cathode material provided in Embodiment 1 of the present invention at an etching time of 160 seconds;
[0023] Figure 4 The X-ray photoelectron spectra of the cathode material provided in Embodiment 1 of the present invention at different etching time points;
[0024] Figure 5 The X-ray photoelectron spectra of the cathode material provided in Comparative Example 1 of this invention at different etching time points are shown.
[0025] Explanation of reference numerals in the attached figures:
[0026] 100 - Electrode assembly; 101 - Positive electrode; 102 - Negative electrode; 103 - Separator membrane. Detailed Implementation
[0027] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0028] As described in the background section of this invention, existing cathode materials suffer from low initial coulombic efficiency and insufficient cycle stability during charge and discharge. To address these issues, in a typical embodiment of this invention, a cathode material is provided. This material is etched using argon ions at a rate of 0.25 nm / s. X-ray photoelectron spectroscopy is used to characterize the etched cathode material. The cathode material exhibits lattice oxygen characteristic peaks at etching times of 160 seconds, 320 seconds, and 480 seconds. The absolute value of the peak position difference between any two lattice oxygen characteristic peaks at any given etching time is ΔE. a And ΔE a ≤0.1eV.
[0029] The cathode material includes secondary particles, which consist of a surface region, a transition layer region, and a core region. The etching process begins from the surface of the secondary particles of the cathode material using argon ion etching at a rate of 0.25 nm / s. The surface region is defined as the region with an etching time between 0 and 160 seconds, the region with an etching time between 160 and 480 seconds is the transition layer region, and the region with an etching time greater than 480 seconds is the core region.
[0030] The cathode material includes a substrate material and a coating layer located on at least a portion of the surface of the substrate material. The substrate material includes nickel, cobalt, and manganese, and the coating layer includes at least one element selected from Zr, Al, W, B, Sr, Y, Ti, S, and P. The transition layer region is the area of the coating layer close to the substrate material, i.e., the region with an etching time between 160 seconds and 480 seconds. In the transition layer region, i.e., the region with an etching time between 160 seconds and 480 seconds, the cathode material is more prone to undergoing harmful phase transitions (such as layered to spinel phase) during deep delithiation. The stability of lattice oxygen directly affects the stability of the cathode material during charge and discharge and the lithium-ion insertion / extraction capability. In some embodiments, the coating layer on the surface of the substrate material can be observed by transmission scanning electron microscopy (TEM).
[0031] Therefore, by defining the cathode material as having lattice oxygen characteristic peaks at etching times of 160 seconds, 320 seconds, and 480 seconds, and specifying that the absolute value of the peak position difference between any two lattice oxygen characteristic peaks at any two etching times is ΔE, the cathode material can be identified. a And ΔE a ≤0.1eV indicates that the lattice oxygen electron binding energy of the cathode material in the transition layer region remains highly consistent, thereby ensuring the uniformity and structural stability of the transition layer region, suppressing the harmful phase transition that occurs in the transition layer region of the cathode material during deep delithiation, and thus improving the cycle stability of the cathode material and suppressing the capacity decay of the cathode material.
[0032] The etching depth of the cathode material can be controlled by controlling the etching time. X-ray photoelectron spectroscopy (XPS) is then used to characterize the surface of the etched cathode material, obtaining XPS spectra at corresponding time points, thus revealing the peak position of lattice oxygen at that etching depth. For example, in some embodiments, the peak position of lattice oxygen at an etching time of 160 seconds is E1, at 320 seconds is E2, and at 480 seconds is E3, satisfying |E3-E2|≤0.1eV, |E3-E1|≤0.1eV, and |E2-E1|≤0.1eV.
[0033] In some embodiments, the cathode material also exhibits characteristic peaks of active oxygen at etching times of 160 seconds, 320 seconds, and 480 seconds; at the same etching time, the peak intensity ratio of the active oxygen characteristic peak to the lattice oxygen characteristic peak is Z. i where i is a natural integer; Z is the z-axis of any two etching times among 160 seconds, 320 seconds, and 480 seconds. i The absolute value of the difference is ΔZ, which satisfies ΔZ≤0.2. Here, the peak position of the lattice oxygen characteristic peak refers to the electron binding energy at the point where the peak intensity of the lattice oxygen characteristic peak reaches its highest point, and the peak position of the reactive oxygen characteristic peak refers to the electron binding energy at the point where the peak intensity of the reactive oxygen characteristic peak reaches its highest point.
[0034] The peak intensity ratio Z between the characteristic peaks of lattice oxygen and active oxygen i This reflects the relative content of the two oxygen forms on the material surface at a specific etching depth corresponding to a specific etching time. The peak intensity ratio Z of the lattice oxygen characteristic peak to the active oxygen characteristic peak is characterized by etching times of 160 seconds, 320 seconds, and 480 seconds for the cathode material. i The change in Zi can characterize the structural stability of the cathode material in the transition layer region. At etching times of 160 seconds, 320 seconds, and 480 seconds, the Zi value at any two etching time points... i The absolute value of the difference is defined as ΔZ. By limiting ΔZ ≤ 0.2, it means that in the transition layer region of the cathode material, the peak intensity ratio of the lattice oxygen characteristic peak to the active oxygen characteristic peak does not change much, ensuring the uniformity and structural stability of the transition layer region, suppressing the harmful phase transition that occurs in the transition layer region of the cathode material during deep delithiation, thereby improving the cycle stability of the cathode material and suppressing the capacity decay of the cathode material. For example, in some embodiments, the peak intensity ratio of the lattice oxygen characteristic peak to the active oxygen characteristic peak is Z1 when the etching time is 160 seconds, Z2 when the etching time is 320 seconds, and Z3 when the etching time is 480 seconds, satisfying |Z3-Z2| ≤ 0.2, |Z3-Z1| ≤ 0.2, and |Z2-Z1| ≤ 0.2.
[0035] In some embodiments, Z at any two etching time points of 160 seconds, 320 seconds, and 480 seconds... i The absolute value of the difference is defined as ΔZ, which can be a range consisting of 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, or any two of them.
[0036] In some embodiments, the peak intensity ratio Z of the lattice oxygen characteristic peak to the active oxygen characteristic peak of the cathode material at etching times of 160 seconds, 320 seconds, and 480 seconds is... i The value can be between 1 and 1.3. Specifically, it can be a range of 1, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, or any two of them.
[0037] In some embodiments, at etching times of 160 seconds, 320 seconds, and 480 seconds, the absolute value of the peak position difference between the characteristic peaks of lattice oxygen and active oxygen in the cathode material within the same etching time is ΔE, satisfying: ΔE ≥ 1.8 eV. This indicates a significant chemical difference between lattice oxygen and active oxygen on the surface of the cathode material, with lattice oxygen being more stable and active oxygen exhibiting relatively lower reactivity. This further improves the uniformity and structural stability of the transition layer region, suppresses harmful phase transitions occurring in the transition layer region of the cathode material during deep delithiation, thereby enhancing the cycle stability of the cathode material and suppressing capacity decay. For example, the absolute value of the peak position difference between the lattice oxygen characteristic peak and the active oxygen characteristic peak is ΔE1 when the etching time is 160 seconds, the absolute value of the peak position difference between the lattice oxygen characteristic peak and the active oxygen characteristic peak is ΔE2 when the etching time is 320 seconds, and the absolute value of the peak position difference between the lattice oxygen characteristic peak and the active oxygen characteristic peak is ΔE3 when the etching time is 480 seconds, satisfying ΔE1≥1.8eV, ΔE2≥1.8eV, and ΔE3≥1.8eV.
[0038] Specifically, a higher absolute value of the peak position difference ΔE (≥1.8 eV) reflects a stronger chemical difference and stability between lattice oxygen and active oxygen. Maintaining a high ΔE value means that the characteristic peaks of lattice oxygen and active oxygen on the surface of the cathode material are widely spaced. This indicates that the lattice oxygen structure is more stable and less likely to transform into active oxygen. Conversely, the decrease in the characteristic peak value of active oxygen indicates reduced reactivity, thereby reducing the possibility of harmful phase transitions in the transition layer region and effectively improving the cycle life of the battery. Secondly, a higher absolute value of the peak position difference ΔE (≥1.8 eV) means that the characteristic peak of lattice oxygen is larger and the characteristic peak of active oxygen is smaller. The high binding energy of the characteristic peak of lattice oxygen indicates its stability on the surface of the cathode material, which helps maintain the layered structure of the cathode material during charge and discharge, further suppressing harmful phase transitions in the transition layer region. In addition, a higher absolute value of the peak position difference ΔE can provide a larger redox potential window, allowing the transition layer region of the cathode material to withstand larger potential changes during electrochemical cycling, thereby further improving the battery's high voltage resistance, cycle stability, and energy density.
[0039] In some embodiments, the impedance value of the positive electrode material is R, satisfying R < 25Ω. Impedance is one of the important parameters for measuring the resistance to charge transfer within a battery. By limiting R to 25Ω, this invention indicates that the positive electrode material has a low impedance value, meaning that under the same charge and discharge conditions, the battery voltage drop is smaller, and the energy loss during charge transfer is also lower. A positive electrode material satisfying R < 25Ω can increase the battery's operating voltage, thereby improving the battery's output power and energy density. Secondly, a low impedance value of the positive electrode material helps reduce polarization during charge and discharge, significantly reducing internal polarization and thus extending the battery's cycle life and reducing capacity decay. Furthermore, a lower impedance value helps reduce heat accumulation inside the battery, lowering the possibility of thermal runaway and thus improving battery safety. Therefore, by controlling the impedance value R of the positive electrode material to less than 25Ω, the electrochemical performance, cycle life, energy efficiency, and safety of the battery can be significantly improved. For example, the impedance value R of the positive electrode material can be a range of 15Ω, 16Ω, 17Ω, 18Ω, 19Ω, 20Ω, 21Ω, 22Ω, 23Ω, 24Ω or any combination thereof.
[0040] In some embodiments, the free lithium content of the cathode material is F, satisfying F > 0.1%. By limiting the free lithium content of the cathode material to F > 0.1%, the battery capacity, cycle stability, and structural stability can be further improved, while reducing internal impedance, optimizing storage performance, and enhancing safety. For example, the free lithium content F of the cathode material can be a range of 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, or any combination thereof.
[0041] Specifically, free lithium refers to lithium ions that are not fully integrated into the crystal lattice structure on the surface or edge of the cathode material. These free lithium ions can more easily be inserted and extracted during charge and discharge, thus increasing the reversible capacity of the battery to some extent. A higher free lithium content helps improve the electrochemical activity of the cathode material and increases the overall energy density of the battery. The presence of free lithium can compensate for lithium ion losses that may occur during cycling, such as electrolyte decomposition and side reactions, thereby helping to maintain the electrochemical balance of the battery and reduce capacity decay. Cathode materials with F > 0.1% can better maintain the supply of lithium ions and extend the cycle life of the battery. Secondly, during charge and discharge cycles, the insertion and extraction of lithium ions in the crystal lattice structure leads to lattice expansion and contraction, which may cause lattice distortion and structural damage. An appropriate amount of free lithium helps mitigate these structural changes, maintain the structural integrity and stability of the material, and prevent performance degradation. Furthermore, the increase of free lithium can reduce the reaction of cathode materials with moisture and carbon dioxide in the environment during storage to generate residual alkaline compounds, such as LiOH and Li2CO3, thereby reducing the surface activity of the material, avoiding abnormal capacity decay of the battery during storage, and preventing the increase of internal impedance of the battery and the problem of positive electrode slurry gelation caused by the presence of residual alkaline compounds, reducing the risk of internal short circuits in the battery, and improving the overall safety of the battery.
[0042] In some embodiments, the peak position of the lattice oxygen characteristic peak is 531–533 eV. Specifically, it can be a range of 531 eV, 531.5 eV, 532 eV, 532.5 eV, 533 eV, or any combination thereof. By limiting the peak position range of lattice oxygen, the chemical properties and electrochemical performance of the cathode material can be optimized. A higher peak position of lattice oxygen means a stronger chemical bond formed between oxygen atoms and metal ions, which helps to improve the structural stability of the cathode material during charge and discharge processes and prevent the precipitation of lattice oxygen. This stability is particularly important for cathode materials because as the nickel content gradually increases, lattice oxygen is easily precipitated in the cathode material under high SOC conditions, thereby generating oxygen, oxidizing the electrolyte, leading to battery bulging and safety hazards.
[0043] In some embodiments, the peak position of the active oxygen characteristic peak is 528–530 eV. Specifically, it can be a range of 528 eV, 528.5 eV, 529 eV, 529.5 eV, 530 eV, or any combination thereof. By limiting the peak position range of active oxygen, the chemical properties and electrochemical performance of the cathode material can be optimized. A lower peak position of active oxygen indicates a relatively weaker binding force with the material surface. This weaker binding force helps suppress side reactions between active oxygen and the electrolyte during battery charging and discharging. The reaction between active oxygen and the electrolyte generates gas, increasing the internal pressure of the battery and accelerating battery performance degradation. By controlling the peak position of active oxygen within the 528–530 eV range, this type of side reaction can be effectively reduced, improving the cycle stability and safety of the battery.
[0044] In some embodiments, the chemical formula of the cathode material includes LiNi. 1-x-y-z Co x Mn y M z O2, wherein M includes at least one of Zr, Al, W, B, Sr, Y, Ti, S, and P, 0≤x≤0.2, 0≤y≤0.5, and 0≤z≤0.1. M is a coating element and / or a doping element.
[0045] In some embodiments, the median particle size D50 of the cathode material is 5–7 μm, for example, a range consisting of 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, or any combination thereof. The median particle size D50 refers to the diameter at the median of the particle size distribution of the cathode material. Particle sizes within this range help balance the electrochemical and processing properties of the material. Smaller particle sizes can improve the conductivity and lithium-ion diffusion rate of the material, thereby improving the charge / discharge speed and cycle performance of the secondary battery. However, excessively small particle sizes may lead to an increase in the specific surface area of the material, thereby increasing the risk of surface side reactions and reducing the stability and safety of the secondary battery. On the other hand, while larger particle sizes can reduce surface side reactions, they may reduce the lithium-ion diffusion efficiency, affecting the power density of the secondary battery. Therefore, by controlling the median particle size D50 of the cathode material to be within the range of 5–7 μm, both high electrochemical activity and good processing properties of the cathode material can be balanced, ensuring the overall performance of the secondary battery.
[0046] In some embodiments, the tap density of the positive electrode material is 2–3 g / cm³. 3 For example, 2g / cm 3 2.1g / cm 3 2.2g / cm 3 2.3g / cm 3 2.4g / cm 3 2.5g / cm 32.6g / cm 3 2.7g / cm 3 2.8g / cm 3 2.9g / cm 3 3g / cm 3 Or a range consisting of any two of these. Tap density refers to the density of the cathode material after being tapped at a certain frequency and amplitude. A higher tap density can increase the energy density of the battery because it means that more active material can be loaded in the same volume. By controlling the tap density of the cathode material to 2-3 g / cm³, the energy density of the battery can be improved. 3 This indicates that the cathode material has good interparticle density, which can effectively fill the space of the cathode sheet in the secondary battery, thereby improving the overall energy density of the secondary battery.
[0047] In some embodiments, the compaction density of the cathode material is 3–4 g / cm³. 3 For example, 3g / cm 3 3.1g / cm 3 3.2g / cm 3 3.3g / cm 3 3.4g / cm 3 3.5g / cm 3 3.6g / cm 3 3.7g / cm 3 3.8g / cm 3 3.9g / cm 3 4g / cm 3 Or a range consisting of any two of these. Compacted density refers to the density of positive electrode material particles after being compacted under a certain pressure. It reflects the density of the positive electrode sheet in a compacted state during battery assembly. Higher compacted density also helps to improve the energy density of secondary batteries, by controlling the compacted density to be between 3 and 4 g / cm³. 3 This indicates that the cathode material can withstand high pressure while maintaining structural integrity, and at the same time provide sufficient lithium-ion diffusion paths to maintain good electrochemical performance.
[0048] In some embodiments, the specific surface area of the cathode material is 0.5–0.8 m². 2 / g, for example 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2The specific surface area of a cathode material is a range consisting of 0.5–0.8 m² / g or any combination thereof. The specific surface area of a cathode material refers to the surface area per unit mass of cathode material. In cathode materials, an appropriate specific surface area ensures good diffusion pathways for lithium ions on the material surface and within the material, without leading to excessive surface side reactions that could affect battery stability and energy efficiency. This is achieved by controlling the specific surface area of the cathode material to be between 0.5 and 0.8 m² / g. 2 The / g indicates that the cathode material has reasonable surface activity, which can provide sufficient electrochemical reaction sites while maintaining a low risk of surface side reactions, thus ensuring the safety and cycle performance of the secondary battery during charge and discharge.
[0049] In some embodiments, charge-discharge tests are performed in the range of 3.0 to 4.3V, and the first coulombic efficiency of the cathode material is ≥90.1%, the first discharge capacity is ≥215.0 mAh / g, and the capacity retention rate after 50 cycles is ≥91.2%.
[0050] This invention does not limit the specific preparation process of the cathode material, as long as the above parameters are met. In some embodiments, the preparation method of the above cathode material includes the following steps:
[0051] S1, the ternary material precursor, lithium source and dopant are mixed to obtain the first mixture;
[0052] S2, the first mixture is subjected to a first calcination to obtain an intermediate product;
[0053] S3, the intermediate product is mixed with the first coating agent and then calcined for a second time to obtain the second calcined product;
[0054] S4. The second calcination product is placed in a hot-coated single cone, and the second coating agent is added into the single cone and stirred. The single cone is heated by heat transfer oil to carry out a pre-reaction to obtain the second coated product. The second coated product is then subjected to a third calcination, sieved and demagnetized to obtain the positive electrode material.
[0055] In step S1, the ternary material precursor is typically obtained by mixing nickel, cobalt, and manganese metal salts and hydroxides in a specific ratio, followed by a series of chemical reactions and heat treatments. The lithium source refers to a compound that provides lithium ions, such as lithium carbonate (Li₂CO₃), lithium hydroxide (LiOH), or lithium nitrate (LiNO₃). Dopants include, but are not limited to, metal oxides, lithium salts, and metal salts used for surface modification. In the above embodiments, the doping amount of M can be adjusted by precisely controlling the amount of dopant used.
[0056] In step S2, the first mixture undergoes a first calcination treatment at high temperature. The purpose is to react the ternary precursor and the lithium source to form a lithium transition metal oxide with a layered structure. Simultaneously, element M also participates in the reaction, forming a composite material or coating layer. The first calcination process is typically carried out in an air or oxygen atmosphere, and the temperature and time can be adjusted according to actual needs. The material obtained after calcination usually requires further processing to become the final intermediate product, such as crushing, sieving, and demagnetization.
[0057] In step S3, the intermediate product is mixed with the first coating agent. This can be achieved through methods such as stirring, vibration, or using a rotary mixer, to dry-coat the intermediate product and ensure that the first coating agent is evenly distributed on the surface of the intermediate product, forming a protective coating. A low-temperature secondary calcination is then performed to promote the fusion reaction between the coating agent and the calcined matrix.
[0058] In step S4, the thermally coated single cone reactor may include a reactor shell, which has a single-cone structure and a feeding port at the top. The calcined product is placed inside the single-cone reactor, and a second coating agent is added and mixed with the calcined product to form a homogeneous mixture. Simultaneously, the inside of the single cone is heated to a specific temperature and maintained for a certain time to promote a tight bond between the second coating agent and the calcined product, forming a second coated product. The second coated product undergoes a third calcination to further solidify the coating layer. After the third calcination, further processing is usually required to obtain the final cathode material, such as crushing, sieving, and demagnetization.
[0059] In existing technologies, as the nickel content increases, residual alkaline compounds appear on the surface of the cathode material. These are mostly reduced through water washing. However, during washing, secondary particles of the cathode material come into contact with excessive water, causing some material to react with the water and triggering severe lattice lithium dissolution. This not only reduces the overall lithium-ion content of the material but also decreases the number of lithium ions that can be intercalated or deintercalated during charging and discharging, thus reducing battery capacity and weakening the high energy density advantage of the cathode material. Secondly, due to its high reactivity, the cathode material is prone to the precipitation of reactive oxygen species during washing, damaging the layered structure and gradually transforming it into a disordered spinel or rock salt structure. These two structures lack electrochemical reactivity during battery cycling and are poor conductors of lithium ions, thereby reducing the mass transfer rate of lithium ions on the material surface, increasing surface impedance, and exacerbating polarization problems during battery charging and discharging.
[0060] This invention achieves the preparation of cathode materials through a combination of dry coating and single-cone thermal coating. By adding different coating agents at different stages, the corresponding additives can react at appropriate temperatures, thereby maximizing the coating effect and eliminating the need for water washing. This effectively mitigates the adverse effects of high residual alkali and high reactivity on the cathode material surface, while avoiding problems such as lithium leaching and deterioration of the layered structure. Secondly, the invention promotes the formation of the lattice structure through the first calcination, which helps the lattice integrity and stability of the material, providing a well-structured substrate for subsequent coating. Then, the first coating agent improves the chemical environment of the material surface, reducing surface side reactions, such as reducing the precipitation of active oxygen, thereby ensuring the stability of the lattice oxygen on the surface of the prepared cathode material. Finally, a second coating agent is used to coat the calcined substrate through a single-cone preheating reaction, forming a uniform coating layer. During the single-cone thermal coating process, the second coating agent chemically bonds with the material surface, forming a stable protective layer. This inhibits the surface migration and reactivity of lattice oxygen, helps maintain the stability of the lattice oxygen peak positions at different depths, and ensures the high stability of the lattice oxygen on the surface of the prepared cathode material. Furthermore, the chemical bonds in the prepared cathode material are further strengthened during the third calcination process. Therefore, the above preparation method, by controlling the chemical composition of the material, the three-stage calcination, and the use of the coating agent during the coating process, helps improve the structural stability of the transition layer region of the prepared cathode material, resulting in smaller changes in the lattice oxygen peak positions at different depths. This, in turn, improves the electrochemical performance of secondary batteries using the prepared cathode material, such as cycle stability, impedance, and energy density.
[0061] This invention does not limit the specific types of dopants, first coating agents, and second coating agents, and they can be selected according to actual needs. For example, in some embodiments, the dopant includes at least one of compounds containing zirconium, compounds containing strontium, compounds containing yttrium, and compounds containing titanium; the first coating agent includes at least one of compounds containing aluminum, compounds containing boron, and compounds containing titanium; and the second coating agent includes at least one of compounds containing sulfur and compounds containing phosphorus. This invention does not impose further limitations on these aspects.
[0062] The second coating agent is selected from low-temperature reaction coating compounds. This invention does not limit the content of the second coating agent and can be adjusted according to actual needs. For example, in some embodiments, the content of the second coating agent is 1000-2000 ppm. The second coating agent is added to the single cone through the excipient inlet, stirred, and pre-reacted by heating with heat-conducting oil.
[0063] The present invention does not limit the conditions for calcination and single-cone heat coating treatment. For example, in some embodiments, the temperature of the first calcination is 700-1000°C and the time is 4-12 hours; the temperature of the single-cone heat coating treatment is 140-180°C and the time is 2-5 hours.
[0064] A second aspect of the present invention provides a positive electrode sheet comprising the positive electrode material provided in the first aspect.
[0065] The positive electrode sheet of the present invention includes a positive current collector and a positive electrode material active layer disposed on at least one surface of the positive current collector. The positive current collector can be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as, but not limited to, a current collector formed by combining the aforementioned conductive foil and polymer substrate. The positive electrode material active layer comprises the positive electrode material as described above.
[0066] The positive electrode material active layer also includes an adhesive for bonding the positive electrode active material particles to facilitate the formation of the film layer, and also to improve the bonding force between the positive electrode material active layer and the positive electrode current collector. In some embodiments, the adhesive may include, but is not limited to, at least one of polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, or nylon.
[0067] The positive electrode material active layer may further include a conductive material, which includes, but is not limited to, carbon-based materials, metal-based materials, conductive polymers, or any combination thereof. In some embodiments, carbon-based materials may include, but are not limited to, natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, metal-based materials may include, but are not limited to, metal powders or metal fibers, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.
[0068] In the specific preparation of the positive electrode sheet, the positive electrode material, conductive material, and binder can be dispersed in an appropriate amount of solvent and thoroughly stirred to form a uniform positive electrode slurry. The positive electrode slurry is then uniformly coated onto the positive electrode current collector, and after drying, rolling, and slitting, the positive electrode sheet is obtained. In one specific embodiment, the positive electrode active layer comprises, by mass percentage, 70%–99% positive electrode material, 0.5%–15% conductive agent, and 0.5%–15% binder.
[0069] A third aspect of the present invention provides a secondary battery comprising the positive electrode provided in the second aspect above.
[0070] Due to the inclusion of the aforementioned high-performance positive electrode, this secondary battery possesses advantages such as high capacity, high initial efficiency, and long cycle life. The secondary battery can be a lithium-ion battery, sodium-ion battery, solid-state electrolyte battery, etc., and is not limited thereto.
[0071] Specifically, the secondary battery includes a casing, an electrode assembly, and an electrolyte. Both the electrode assembly and the electrolyte are located inside the casing.
[0072] The outer casing can be a packaging bag encapsulated with a sealing film (such as aluminum-plastic film), for example, a pouch battery. In other embodiments, it can also be a steel-cased battery, an aluminum-cased battery, etc.
[0073] Please see Figure 1 and Figure 2 The electrode assembly 100 includes a positive electrode 101, a negative electrode 102, and a separator 103, with the separator 103 disposed between the positive electrode 101 and the negative electrode 102. For charging, please refer to [reference needed]. Figure 1 Active ions (such as lithium ions) are extracted from the lattice of the positive electrode material (such as a lithium-ion intercalation compound) in the positive electrode 101, pass through the electrolyte and the separator 103, reach the negative electrode 102, and insert into the lattice of the negative electrode material. For discharge procedures, please refer to [link to relevant documentation]. Figure 2 Active ions (such as lithium ions) are deintercalated from the lattice of the negative electrode material of the negative electrode 102, pass through the electrolyte through the separator 103, reach the positive electrode 101 and are embedded in the lattice of the positive electrode material (such as lithium intercalation compound), generating electrons that travel from the negative electrode 102 to the positive electrode 101 through the external circuit. The reverse movement of electrons forms an electric current, which can be used by electrical appliances.
[0074] In some embodiments, the electrode assembly 100 may be a stacked structure, which is formed by alternatingly stacking a positive electrode 101, a separator 103, and a negative electrode 102. In other embodiments, the electrode assembly 100 may also be a wound structure, which is formed by sequentially stacking and then winding the positive electrode 101, the separator 103, and the negative electrode 102.
[0075] The positive electrode 101 includes a positive current collector and a positive electrode material active layer disposed on at least one surface of the positive current collector. The positive current collector can be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as, but not limited to, a current collector formed by combining the aforementioned conductive foil and polymer substrate. The positive electrode material active layer includes the positive electrode material described in the first aspect above.
[0076] The negative electrode 102 includes a negative electrode current collector and an active layer of negative electrode material disposed on at least one surface of the negative electrode current collector. The negative electrode current collector can be at least one of copper foil, nickel foil, stainless steel foil, titanium foil, or carbon-based current collector, or any composite current collector disclosed in the prior art, such as, but not limited to, a current collector formed by combining the aforementioned conductive foil and polymer substrate.
[0077] The negative electrode active material layer includes a negative electrode material, which may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present invention is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0078] The active layer of the negative electrode material also includes a binder to bond the negative electrode active material particles, thereby facilitating the formation of the film layer and improving the bonding force between the active layer of the negative electrode material and the negative electrode current collector. In some embodiments, the binder may include, but is not limited to, polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, or nylon, etc.
[0079] The active layer of the negative electrode material may further include a conductive material, which includes, but is not limited to, carbon-based materials, metal-based materials, conductive polymers, or any combination thereof. In some embodiments, carbon-based materials may include, but are not limited to, natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, metal-based materials may include, but are not limited to, metal powders or metal fibers, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.
[0080] The separator 103 includes a membrane layer with a porous structure, and its material includes, but is not limited to, at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide, or aramid. For example, the separator 103 may be a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, or a polypropylene-polyethylene-polypropylene porous composite membrane, etc.
[0081] The electrolyte serves to conduct ions between the positive electrode 101 and the negative electrode 102. The electrolyte can be in one or more states, including gel, solid, and liquid. In some embodiments, the electrolyte is a liquid electrolyte solution. The liquid electrolyte solution serves to conduct active ions between the positive electrode 101 and the negative electrode 102. In some embodiments, the liquid electrolyte solution includes a lithium salt and an organic solvent. The lithium salt may be selected from, but is not limited to, one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium perchlorate (LiClO4), lithium tetraphenylborate (LiB(C6H5)4), lithium methanesulfonate (LiCH3SO3), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonyl)imide (LiN(SO2CF3)2), lithium tri(trifluoromethanesulfonyl)methyllithium (LiC(SO2CF3)3), lithium dioxolaneborate (LiBOB), and lithium difluorophosphate (LiPO2F2). For example, LiPF6 is selected as the lithium salt because it provides high ionic conductivity and improves cycling characteristics. The organic solvent may be a carbonate compound, a carboxylic acid ester compound, an ether compound, a nitrile compound, other organic solvents, or combinations thereof. Examples of carbonate compounds include, but are not limited to, diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butyl carbonate (BC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate, or combinations thereof.
[0082] In the preparation of secondary batteries, positive electrode sheets, separators and negative electrode sheets are wound or stacked to obtain battery cells. The battery cells are then encapsulated in pre-stamped aluminum-plastic films. After the encapsulated batteries are dried, electrolyte is injected into the dried batteries. The secondary batteries are then aged, formed and resealed to complete the preparation of the secondary batteries.
[0083] The present application will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed in the present application.
[0084] In the following embodiments, the single-cone atomizing reactor used includes a reactor shell, which has a single-cone structure. A liquid phase inlet pipe is provided at the top of the reactor shell, and a conical nozzle is provided at the inlet end of the liquid phase inlet pipe.
[0085] Example 1
[0086] The method for preparing the cathode material in this embodiment includes the following steps:
[0087] S1, Ni 0.88 Co 0.09 Mn 0.03 (OH)2, lithium salt, and zirconium dioxide are mixed in a molar ratio of n(Li):[n(Ni)+n(Co)+n(Mn)]:n(Zr) of 1.06:1:0.002 and mixed for 30 minutes at 300 rpm to obtain mixture A.
[0088] S2, the mixture A is calcined at 730°C in an oxygen atmosphere for 8 hours, cooled and then sieved by roller screen to obtain the intermediate product;
[0089] S3, the intermediate product is fed into a coating machine and a first coating agent is added. Dry coating is carried out under stirring and mixing to obtain a first coated product. The first coating agent includes nano-alumina and nano-titanium oxide in a mass ratio of 3:4. The mass contents of nano-alumina and nano-titanium oxide are 1500 ppm and 2000 ppm, respectively, based on 100% of the mass of the intermediate product. The coated product is then subjected to a second calcination to obtain a second calcined product. The second calcination temperature is 450℃ and the product is calcined in an oxygen atmosphere for 4 hours.
[0090] S4, the calcined product is fed into the hot-coated single cone, the second coating agent is added into the hot-coated single cone through the auxiliary material inlet, and mixed with the calcined product. At the same time, the hot-coated single cone is heated to 150°C and reacted for 4 hours to obtain the second coated product.
[0091] The second coating product was calcined three times for 8 hours at 400℃ in an oxygen atmosphere, and then demagnetized by sieving to obtain the positive electrode material. The second coating agent included ammonium phosphate; based on the mass of the first coating product as 100%, the mass content of the second coating agent was 2500 ppm.
[0092] Example 2
[0093] The difference from Example 1 is that in S4, the heat-coated single cone is heated to 150°C and reacted for 3 hours.
[0094] Example 3
[0095] The difference from Example 1 is that in S4, the heat-coated single cone is heated to 150°C and reacted for 5 hours.
[0096] Example 4
[0097] The difference from Example 1 is that in S4, the heat-coated single cone is heated to 140°C and reacted for 4 hours.
[0098] Example 5
[0099] The difference from Example 1 is that in S4, the heat-coated single cone is heated to 160°C and reacted for 4 hours.
[0100] Example 6
[0101] The difference from Example 1 is that the content of the second coating agent in S4 is 2000 ppm.
[0102] Example 7
[0103] The difference from Example 1 is that the content of the second coating agent in S4 is 2500 ppm.
[0104] Example 8
[0105] The difference from Example 1 is that the roasting temperature in S2 is replaced with 430°C.
[0106] Example 9
[0107] The difference from Example 1 is that the roasting temperature in S2 is replaced with 370°C.
[0108] Example 10
[0109] The difference from Example 1 is that Ni in S1 0.88 Co 0.09 Mn 0.03 (OH)2, lithium salt, and zirconium dioxide are mixed in a molar ratio of n(Li):[n(Ni)+n(Co)+n(Mn)]:n(Zr) of 1.05:1:0.002.
[0110] Example 11
[0111] The difference from Example 1 is that the first coating agent in S3 includes nano-alumina and nano-titanium oxide in a mass ratio of 1:1:1; based on the mass of the intermediate product as 100%, the mass contents of nano-alumina and nano-titanium oxide are 1500ppm and 1500ppm, respectively.
[0112] Example 12
[0113] The difference from Example 1 is that the first coating agent in S3 includes nano-alumina and nano-titanium oxide in a mass ratio of 3:5:3; based on the mass of the intermediate product as 100%, the mass contents of nano-alumina and nano-titanium oxide are 1500ppm and 2500ppm, respectively.
[0114] Comparative Example 1
[0115] The method for preparing the cathode material in this embodiment includes the following steps:
[0116] S1, Ni 0.88 Co 0.09 Mn 0.03 (OH)2, lithium salt, and zirconium dioxide are mixed in a molar ratio of n(Li):[n(Ni)+n(Co)+n(Mn)]:n(Zr) of 1.06:1:0.002 and mixed for 30 minutes at 300 rpm to obtain mixture A.
[0117] S2, the mixture A is calcined at 730°C in an oxygen atmosphere for 8 hours, cooled and then sieved by roller screen to obtain the first intermediate product;
[0118] S3, the first intermediate product is mixed with the coating material and calcined at 720°C in an oxygen atmosphere for 8 hours, then sieved and demagnetized to obtain the second intermediate product; wherein, the coating material includes nano-alumina and nano-titanium oxide; based on the mass of the first intermediate product as 100%, the mass contents of nano-alumina and nano-titanium oxide are 1500ppm and 1500ppm, respectively.
[0119] S4. The second intermediate product is mixed with water at a water-to-material ratio of 1:1 and washed for 0.3 hours to obtain the cathode material.
[0120] Comparative Example 2
[0121] The difference from Comparative Example 1 is that in S4, the second intermediate product is mixed with water at a water-to-material ratio of 0.9:1.
[0122] Comparative Example 3
[0123] The difference from Comparative Example 1 is that in S4, the second intermediate product is mixed with water at a water-to-material ratio of 1.1:1.
[0124] Comparative Example 4
[0125] The difference from Comparative Example 1 is that the water washing in S4 lasted for 0.2 hours.
[0126] Test case
[0127] 1. Testing of characteristic peaks of lattice oxygen and reactive oxygen species
[0128] Argon ions (Ar) +Etching was performed from the surface of the secondary particles of the cathode material toward the center of the particles at an etching rate of 0.25 nm / s. The surface of the etched cathode material was characterized by X-ray photoelectron spectroscopy at etching times of 160 seconds, 320 seconds, and 480 seconds, respectively, to obtain the lattice oxygen characteristic peak and active oxygen characteristic peak at etching times of 160 seconds, 320 seconds, and 480 seconds.
[0129] The spectral peaks were analyzed using Avnatage analysis software to determine the specific peak positions and intensities. The absolute values of the peak position differences between the lattice oxygen characteristic peak and the reactive oxygen characteristic peak at etching times of 160 seconds, 320 seconds, and 480 seconds were calculated, and the minimum value was taken to obtain the absolute value ΔE of the peak position difference between the lattice oxygen characteristic peak and the reactive oxygen characteristic peak at the same etching time. The peak positions of the lattice oxygen characteristic peak and the reactive oxygen characteristic peak are located in the ranges of 531–533 eV and 528–530 eV, respectively. The peak intensity of the lattice oxygen characteristic peak is taken as the highest point within the range of 531–533 eV, and the corresponding binding energy is taken as the binding energy of the lattice oxygen characteristic peak. The binding energy of the reactive oxygen characteristic peak is taken as the highest point within the range of 528–530 eV.
[0130] The peak intensity ratios Z1, Z2, and Z3 of the active oxygen characteristic peak and the lattice oxygen characteristic peak at etching times of 160 seconds, 320 seconds, and 480 seconds were calculated respectively. The absolute values of the differences between any two of Z1, Z2, and Z3 were calculated, and the maximum value was taken to obtain Z at any two etching times. i The absolute value of the difference ΔZ between (i = 1, 2, 3);
[0131] Calculate the absolute value of the peak position difference between the lattice oxygen characteristic peaks at any two etching times of 160 seconds, 320 seconds, and 480 seconds, and take the maximum value to obtain the absolute value ΔE of the peak position difference between the lattice oxygen characteristic peaks at any two etching times. a .
[0132] Figure 4 X-ray photoelectron spectra of the cathode material provided in Example 1 of the present invention at etching times of 160 seconds, 320 seconds and 480 seconds;
[0133] Figure 5 X-ray photoelectron spectra of the cathode material provided in Comparative Example 1 of the present invention at etching times of 160 seconds, 320 seconds and 480 seconds;
[0134] Figure 3The X-ray photoelectron spectrum of the cathode material provided in Example 1 of this invention is obtained at an etching time of 160 seconds. Here, ΔE1 is the absolute value of the peak position difference between the lattice oxygen characteristic peak and the active oxygen characteristic peak in Comparative Example 1 at an etching time of 160 seconds, and ΔE2 is the absolute value of the peak position difference between the lattice oxygen characteristic peak and the active oxygen characteristic peak in Example 1 at an etching time of 160 seconds.
[0135] 2. Impedance test
[0136] The positive electrode material, conductive carbon black, and PVDF of the examples and comparative examples were dissolved in N-methylpyrrolidone at a mass ratio of 94:3.0:3.0, respectively, and the solid content was controlled at 50% to obtain a positive electrode slurry. The positive electrode slurry was coated on an aluminum foil current collector, and after vacuum drying at 95°C, rolling and pressurizing, a positive electrode sheet was obtained. Using a lithium metal sheet as the counter electrode, a coin cell was assembled in an argon-filled glove box.
[0137] The button cell was activated by charging and discharging at a current density of 0.1C within a charge-discharge range of 3.0 to 4.3V. After activation, the cell was placed on a battery cycle test system to test its DCIR impedance value.
[0138] 3. Mass content test of free lithium
[0139] 5g of the cathode material was dispersed in 100mL of deionized water, and residual carbonate and hydroxide ions were dissolved by magnetic stirring. After filtration, the filtrate was obtained, and hydrochloric acid solution was added to it in an automatic potentiometric titrator. Titration was performed by equivalence drop titration. The content of carbonate and hydroxide ions was calculated by the abrupt change point (i.e., the point where the pH value changes suddenly) and the degree of hydrochloric acid consumption. Based on the content of carbonate and hydroxide ions, the mass content of free lithium in the cathode material was calculated.
[0140] 4. First Coulomb efficiency test
[0141] The positive electrode material, conductive carbon black, and PVDF of the examples and comparative examples were dissolved in N-methylpyrrolidone at a mass ratio of 94:3.0:3.0, respectively, and the solid content was controlled at 50% to obtain a positive electrode slurry. The positive electrode slurry was coated on an aluminum foil current collector, and after vacuum drying at 95°C, rolling and pressurizing, a positive electrode sheet was obtained. Using a lithium metal sheet as the counter electrode, a coin cell was assembled in an argon-filled glove box.
[0142] The coin cell was charged and discharged at a current density of 0.1C within a range of 3.0 to 4.3V to obtain the initial reversible specific capacity, the initial charge capacity, and the initial discharge capacity. The initial coulombic efficiency was calculated as follows: initial coulombic efficiency = initial discharge capacity / initial charge capacity.
[0143] 5. Cyclic stability test
[0144] The positive electrode material, conductive carbon black, and PVDF of the examples and comparative examples were dissolved in N-methylpyrrolidone at a mass ratio of 94:3.0:3.0, respectively, and the solid content was controlled at 50% to obtain a positive electrode slurry. The positive electrode slurry was coated on an aluminum foil current collector, and after vacuum drying at 95°C, rolling and pressing, a positive electrode sheet was obtained.
[0145] Using lithium metal sheets as the counter electrode, coin cells were assembled in an argon-filled glove box. The coin cells were activated by charge-discharge cycles at a current density of 0.1C, within a range of 3.0–4.3V. After activation, the cells were placed on a battery cycle testing system. They were charged at a constant current rate of 1C to 4.30V, then charged at a constant voltage with the current gradually decreasing to 0.05C, and finally discharged at a 1C rate to 3.0V. This charge-discharge cycle was repeated 50 times. The discharge capacity Q1 at the first cycle and Q50 at the 50th cycle were measured. The 50-cycle capacity retention rate was calculated as Q50 / Q1 × 100%.
[0146] The test results are shown in Table 1.
[0147] Table 1
[0148]
[0149]
[0150] As shown in Table 1, the cathode materials in Examples 1 to 7 all satisfy ΔE. a ≤0.1eV, while the cathode materials of Comparative Examples 1 to 4 do not satisfy ΔE a ≤0.1eV, Examples 1-7 exhibit higher capacity, higher initial coulombic efficiency, higher 400-cycle capacity retention, and better overall electrical performance compared to Comparative Examples 1-4. Therefore, this invention achieves this by ensuring that all cathode materials satisfy ΔE... a With a voltage of ≤0.1eV, it can significantly improve capacity, initial coulombic efficiency, and cycle stability.
[0151] Furthermore, compared to Example 8, the cathode materials of Examples 1-7 satisfy ΔE a While maintaining a voltage ≤0.1 eV, further achieving ΔE ≥1.8 eV can improve cycle stability while preserving capacity and initial coulombic efficiency. Compared to Examples 9-10, the cathode materials of Examples 1-7 satisfy ΔE... a While maintaining a voltage of ≤0.1eV, further improving ΔZ≤0.2 can enhance cycle stability while preserving capacity and initial coulombic efficiency.
[0152] Furthermore, compared to Example 11, the cathode materials of Examples 1-7 satisfy ΔEa While maintaining a voltage ≤0.1 eV, further improving R ≤25 Ω can enhance cycle stability while preserving capacity and initial coulombic efficiency. Compared to Example 12, the cathode materials of Examples 1-7 satisfy ΔE a While maintaining a voltage of ≤0.1eV, further improving F≥0.1% can enhance cycle stability while preserving capacity and initial coulombic efficiency.
[0153] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A positive electrode material, characterized in that, The cathode material was etched by argon ions at a rate of 0.25 nm / s. X-ray photoelectron spectroscopy was used to characterize the etched cathode material. The cathode material exhibited lattice oxygen characteristic peaks at etching times of 160 seconds, 320 seconds, and 480 seconds. The absolute value of the peak position difference between any two lattice oxygen characteristic peaks at any given etching time point was ΔE. a And ΔE a ≤0.1eV.
2. The cathode material according to claim 1, characterized in that, The cathode material also exhibits characteristic peaks of active oxygen at etching times of 160 seconds, 320 seconds, and 480 seconds; among which... At the same etching time, the peak intensity ratio of the active oxygen characteristic peak to the lattice oxygen characteristic peak is Z. i , where i is a natural integer; and, Z at any two etching time points i The absolute value of the difference is ΔZ, which satisfies ΔZ≤0.
2.
3. The cathode material according to claim 2, characterized in that, At the same etching time point, the absolute value of the peak position difference between the lattice oxygen characteristic peak and the active oxygen characteristic peak of the cathode material is ΔE, which satisfies: ΔE≥1.8eV.
4. The cathode material according to any one of claims 1 to 3, characterized in that, The impedance value of the positive electrode material is R, which satisfies R < 25Ω.
5. The cathode material according to any one of claims 1 to 3, characterized in that, The free lithium content of the cathode material is F, which satisfies F > 0.1%.
6. The cathode material according to claim 2, characterized in that, The peak position of the lattice oxygen characteristic peak is 531-533 eV, and the peak position of the active oxygen characteristic peak is 528-530 eV.
7. The cathode material according to any one of claims 1 to 3, characterized in that, The chemical formula of the cathode material includes LiNi. 1-x-y-z Co x Mn y M z O2, M includes at least one of Zr, Al, W, B, Sr, Y, Ti, S, P, 0≤x≤0.2, 0≤y≤0.5, 0≤z≤0.
1.
8. The cathode material according to any one of claims 1 to 3, characterized in that, The cathode material satisfies at least one of the following characteristics: (1) The median particle size D50 of the volume distribution of the cathode material is 5-7 μm; (2) The tap density of the positive electrode material is 2-3 g / cm³. 3 ; (3) The compaction density of the positive electrode material is 3-4 g / cm³. 3 ; (4) The specific surface area of the positive electrode material is 0.5–0.8 m². 2 / g.
9. A positive electrode plate, characterized in that, The positive electrode sheet comprises the positive electrode material according to any one of claims 1 to 8.
10. A secondary battery, characterized in that, The secondary battery includes the positive electrode sheet as described in claim 9.